Expression of accessory molecules for T-cell activation in peripheral nerve of patients with CIDP and vasculitic neuropathy - Van Rhijn, Ildiko; Van den Berg, Leonard H.; Bosboom, Wendy M. J.; Otten, Henny G.; Logtenberg, Ton (Brain (London, England : 1878), 2000)
Vasculitic neuropathy and chronic inflammatory demyelinating polyneuropathy (CIDP) are neuropathies characterized by a T-lymphocyte infiltrate in the peripheral nerves. The microenvironment in which these T cells become activated, and the molecules and cells that play a role in this process are incompletely understood. Using immunohistochemical analysis, we studied the effect of the presence of adhesion, costimulatory and antigen-presenting molecules on different cell types as a precondition for local T-cell activation in human sural nerve biopsies of seven patients with CIDP, three patients with vasculitic neuropathy and three healthy controls. In biopsies from CIDP and vasculitic neuropathy patients, but not in those from healthy controls, Schwann cells expressed the adhesion/T-cell stimulatory molecule CD58 (LFA-3). The CD58 molecule was also present on endothelial cells of all vasculitic neuropathy patients and one CIDP patient. In biopsies from normal controls and patients, CD54 (ICAM-1) expression was detectable on microvascular endothelial cells. In addition, expression of the costimulatory molecule CD86 was detected on vascular tissue in patients with vasculitic neuropathy. Although macrophages were always present in all subjects, expression of the major histocompatibility complex (MHC)-like molecule CD1a by macrophages was restricted to biopsies from two CIDP patients and one vasculitic neuropathy patient. Unexpectedly, Schwann cells of a single vasculitis patient strongly expressed CD1b, a molecule involved in the presentation of self-glycolipids to T cells. Schwann cells in biopsies from patients and normal controls expressed high levels of the invariant chain, CD74, a molecule involved in the intracellular sorting of MHC class II molecules. There was no evidence for the presence of dendritic cells in sural nerve biopsies. These findings support a model in which T-cell activation can be initiated and/or perpetuated locally in sural nerve biopsies of patients with CIDP and vasculitic neuropathy, and predict an important role for Schwann cells and endothelial cells.